Barriers and Paradigmatic Tensions in Accounting: Reports by a non Mainstream Researcher - Magrini, Vagner de Oliveira; Silva, Marli Auxiliadora da; Silva, Sandra Maria Cerqueira da; Soares, Eduardo Codevilla (Advances in Scientific and Applied Accounting, 2024)
Purpose: This article aims to identify the difficulties encountered by accountants when performing research that subverts the accounting paradigmatic domination patterns. Method: The study uses Pierre Bourdieu’s theoretical concepts of field, habitus and capital. From a methodological perspective, a critical interpretative approach is used, under a qualitative approach, through the use of in depth interviews. To analyze the narrative, dialogical discourse analysis was used in the Bakhtinian aspect. Results: The study reveals the difficulties faced by the interviewee, both in academic relationships with professors and with graduate colleagues, especially because does not employ the mainstream paradigm in the research. The evidence demonstrates the existence of barriers to the dissemination of their research at conferences and in journals in the field, which sometimes did not even receive opinions. The researcher's difficulties in obtaining financing for her studies also stand out, under the justification that the non-mainstream research developed by her is not an accounting study. Such difficulties, addressed in the text, reinforce the situation of domination in the field of accounting research, guided by the functionalist and positivist paradigm, as well as highlighting the effort to maintain the status quo on the part of those in a position of domination in the field. Contributions: In addition to the methodological proposal that subverts the predominant paradigm in accounting research, the discussions in this study can contribute to understanding and overcoming difficulties by exposing how thinking and actions linked to the mainstream reproduce prejudices and try to make invisible the perspectives They seek to expand the theoretical and methodological horizon of accounting research.